2016
DOI: 10.1371/journal.pone.0147574
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Coenzyme Q10 in Patients with Multiple System Atrophy

Abstract: The COQ2 gene encodes an essential enzyme for biogenesis, coenzyme Q10 (CoQ10). Recessive mutations in this gene have recently been identified in families with multiple system atrophy (MSA). Moreover, specific heterozygous variants in the COQ2 gene have also been reported to confer susceptibility to sporadic MSA in Japanese cohorts. These findings have suggested the potential usefulness of CoQ10 as a blood-based biomarker for diagnosing MSA. This study measured serum levels of CoQ10 in 18 patients with MSA, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 15 publications
5
44
0
1
Order By: Relevance
“…Dysfunction of glucocerebrosidase, and probably of the autophagosomal pathway, may represent 1 "hit" in what is likely a pathway that requires multiple "hits" for the development of MSA. Other mechanisms that have been implicated in the development of MSA include mitochondrial dysfunction, [25][26][27][28] toxicity of fibrilized a-synuclein, 29 oxidative stress, 30 neuroinflammation, 31,32 and even prion-like propagation of MSA. 33 Although the current study makes an argument for the involvement of the pathways for clearance of a-synuclein in the development of MSA, it also makes clear that other mechanisms also need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of glucocerebrosidase, and probably of the autophagosomal pathway, may represent 1 "hit" in what is likely a pathway that requires multiple "hits" for the development of MSA. Other mechanisms that have been implicated in the development of MSA include mitochondrial dysfunction, [25][26][27][28] toxicity of fibrilized a-synuclein, 29 oxidative stress, 30 neuroinflammation, 31,32 and even prion-like propagation of MSA. 33 Although the current study makes an argument for the involvement of the pathways for clearance of a-synuclein in the development of MSA, it also makes clear that other mechanisms also need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, there are several reports that abnormal phosphorylated tau is aggregated in phosphorylated synuclein-positive cells. 38 We also disclosed that phosphorylated SNCA-positive neurons often overexpressed TFAM and COX4. 33 We disclosed by immunofluorescence that phosphorylated SNCA-positive neurons in the hippocampus strongly co-expressed 8-OHdG, a marker for oxidative stress.…”
Section: Discussionmentioning
confidence: 83%
“…12 In addition, patients with the cerebellar and parkinsonism subtypes of MSA had similarly decreased plasma levels of CoQ10. Consistent with these observations, Kasai et al 13 found a decreased ratio of serum CoQ10 to cholesterol in patients with MSA.…”
mentioning
confidence: 57%